Reconstruction of the Medial Patellofemoral Ligament - Monllau, Juan C. (Arthrosc Tech, 2017)
Patellar instability has been shown to be associated with different major factors. However, studies have demonstrated that soft tissue reconstructions are adequate enough to reestablish patellar constraint. In recent years, the medial patellofemoral ligament has been recognized as the primary passive restraint for lateral translation of the patella. Their reconstruction has gain popularity as the procedure is quite simple and fast. Although several surgical techniques have been described for their reconstruction, no clear consensus has been reached as to which is best. We present an implant-free, medial patellofemoral ligament reconstruction technique that uses a gracilis tendon autograft, 2 bone convergent tunnels at the original patellar attachment, and looping the graft around the adductor magnus tendon that is used as a pulley for femoral fixation.